The school legislation of the Catholic Church in the Hussitian times - Ratajczak, Krzysztof (Saeculum Christianum. Pismo Historyczne, 2021)
The aim of the paper is to show the state and changes in the school legislation of the Catholic Church in the crucial period of its history, between 1378 and 1477. The focus of the analysis is especially on the acts of law decreed by the popes, on the canons of the councils, but also on the ius particulare of those ecclesiastical provinces that were affected by the Hussite movement. Also, factors influencing the ecclesiastical law in the realm of education are analysed, such as political, social, economic besides religious. Very important was the question if the changes could be controlled or inspired by the Church or whether the changes of the school legislation were only meant to preserve the status quo.